2011
DOI: 10.1590/s1517-97022011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Moral no mundo adulto: a visão dos jovens sobre os adultos de hoje

Abstract: The present study core issue is, how do today's youth judge adults concerning their moral criteria? The issue is twofold relevant for the ethical and moral education of adolescents, both for knowledge on their moral development and for their apparent desertion from the public sphere, favouring the private one. This study aimed at knowing how youth judge adults on moral grounds, while verifying whether youth do clearly separate public and private spheres. Two different surveys were carried out: survey 1 (S1) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Muller and Alencar (2012) investigate how teachers of the 6th to 9th year of basic education judge that they have learnt regarding justice, and how they judge that they teach this value to their students, concluding that the teachers teach how they learn, through impositive and authoritarian actions. Imanishi, Passarelli and La Taille (2011) questioned how present-day young people perceive the adults' morality, these references being moral as much to the children as to the adolescents, and whether there is a split in this judgment between the public and private spheres. These authors obtained, from the young people, negative judgments in relation to the adults, and evaluated positively only those adults from the private sphere, who are invested with emotional warmth, and concluded that the young people do not trust the adults, do not consider them to be ethical people, and question their values.…”
Section: Resultsmentioning
confidence: 99%
“…Muller and Alencar (2012) investigate how teachers of the 6th to 9th year of basic education judge that they have learnt regarding justice, and how they judge that they teach this value to their students, concluding that the teachers teach how they learn, through impositive and authoritarian actions. Imanishi, Passarelli and La Taille (2011) questioned how present-day young people perceive the adults' morality, these references being moral as much to the children as to the adolescents, and whether there is a split in this judgment between the public and private spheres. These authors obtained, from the young people, negative judgments in relation to the adults, and evaluated positively only those adults from the private sphere, who are invested with emotional warmth, and concluded that the young people do not trust the adults, do not consider them to be ethical people, and question their values.…”
Section: Resultsmentioning
confidence: 99%
“…Beliefs played a substantial role in accurately predicting aggressive behavior simultaneously (Guerra, et al 1995). Young people do not perceive adults as being ethical; overall, they criticize how adults engage in public discourse [19]. Generally, youths should feel that an honest individual with personal integrity has more chances to succeed, and an adult must meet such standards.…”
Section: Responsibility Usually Accounts For What You Do and What Oth...mentioning
confidence: 99%
“…Finalmente, se han destacado los estudios asociados al juicio y los comportamientos morales en la adolescencia, mediante estudios efectuados alrededor de Europa, América, África y Asia; dentro de estos se encuentran los hallazgos en estudiantes superdotados, quienes mostraban capacidades superiores en el juicio moral, en comparación con su grupo de edad, sin embargo esto no predecía su comportamiento moral (Tirri, 2011). Se evidenció desconfianza en los jóvenes ante la moralidad del adulto, expresando aspectos como el egoísmo, interés propio y enfoque en la esfera privada, cuestionando sus relaciones con la esfera pública (Imanishi et al, 2011). Por otro lado, hubo un incremento en el juicio moral de adolescentes y sus creencias epistemológicas, a través de un programa de educación ética basado en ciencia, tecnología y sociedad (Han y Jeong, 2014), así como los ajustes a lineamientos educativos basados en la teoría del desarrollo moral de Kohlberg (Moreira et al, 2020), la resiliencia e inteligencia espiritual de los estudiantes (Darvishzadeh y Bozorgi, 2016) y la acción moral de los educadores (Caetano y Dell'Agli, 2017).…”
Section: Desarrollo Moral Y Educación Secundariaunclassified